Determination of Total Arsenic in Seaweed Products by Neutron Activation Analysis - N. Salim; M. Santoso; S. Damayanti; T.G. Kartawinata (PPIKSN-BATAN, 2013)
Seaweed products are widely consumed as food nowadays. Seaweeds are known to contain arsenic due to their capability to accumulate arsenic from the environment. Arsenic is a known toxic element which naturally occurs in the environment. Ingestion of high levels of arsenic will cause several adverse health effects. Arsenic in food occurs at trace concentrations which require sensitive and selective analysis methods to perform elemental analysis on. Validated neutron activation analysis was used to determine the arsenic contents in seaweed products namely catoni from domestic product and nori from foreign products. The total arsenic concentration in the samples analyzed ranges from 0.79 mg/kg to 30.14 mg/kg with mean concentration 14.39 mg/kg. The estimated exposure to arsenic contributed by the analyzed products is from 0.07% up to 8.54% of the established provisional tolerable daily intake (PTDI) which is still far below the maximum tolerable level. Received: 16 January 2013; Revised: 11 April 2013; Accepted: 13 April 2013